PRODUKSI PROBIOTIK RUMEN BERBASIS BAKTERI LIGNOCHLORITIK DAN APLIKASINYA PADA TERNAK SAPI PERAH - Prihartini, Indah; Khotimah, Khusnul (Jurnal Gamma, 2011)
Indah Prihartini1 & Khusnul Khotimah21 &2 Staf Pengajar Jurusan Produksi Ternak , Fakultas Pertanian-Peternakan, Universitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas 246 MalangEmail: indahprihartini@gmail.com & thuthul17@yahoo.comABSTRACTBacteria-based probiotics lignochloritik have a high ability in the growth, production and enzymeactivity. Probiotics have a high ability in the activity of lignin degradation and organochlorin in anaerobic condition. Degradation activity of probiotics lignochloritik also not antagonistic to the rumenmicrobial activity. So that could be used as a probiotic probiotics rumen. To increase production,quality and safety of the milk production of dairy cows. necessary to test the application in dairycows in vivo. The study found the addition of probiotics in feed concentrate at 1% increase milkproduction by 30-40% per day with an average fat content of 4.1% and reduce pesticide residues inmilk of dairy cows organochlorin 80-100%. The recommended advice is to level the use of probioticsis best to feed 1% of the concentrate feed.Keywords: Probiotics, lignochloritik, lignin, organochlorin